Mucous layer effects towards nasal airflow. - Chih, Fang Lee; Ahmad, Kamarul Arifin; Ismail, Rushdan; Abdul Hamid, Suzina (2012)
Computational fluid dynamics (CFD) has been widely used to study nasal airflow but none of the previous studies are focused on how the mucous layer affects the nasal airflow. Therefore, this research studies the changes in velocity magnitudes caused by mucous layer of different thickness and visualize the effects of mucous layer towards nasal airflow. Six different models with various thickness of mucous layer within the range of 0.005 mm-0.050 mm were implemented in the analysis with mass flow rate of 7.5 to 20 L/min. The results from all the six models were compared with the model with non-mucous effects. Velocity streamlines of non-mucous model are shown for better view of the airflow pattern from inlet to outlet and also circulations can be observed more clearly. Based on both laminar and turbulent airflow simulations at mass flow rate of 10 and 20 L/min, the mucous layer effects are shown to cause significant changes to the velocity magnitude and pressure contours along the nasal cavity. Inclusion of mucous layer does give significant effects to the nasal airflow. Therefore, it should not be neglected in analysis to ensure more accurate information on nasal airflow can be obtained.